2021
DOI: 10.1080/08856257.2021.1872842
|View full text |Cite
|
Sign up to set email alerts
|

Fostering school connectedness online for students with diverse learning needs: inclusive education in Australia during the COVID-19 pandemic

Abstract: Inclusive education in Australia during the COVID-19 pandemicOver the first few months of 2020, the schooling sector shifted to distance education as governments moved to bring the virus, COVID-19, under control. Education sectors rapidly developed online environments. In this milieu teachers have made swift changes to accommodate their students' diverse range of learning needs. In this article we draw on a qualitative study in Australia to identify key challenges and approaches for fostering school connectedn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 26 publications
3
52
0
2
Order By: Relevance
“…Guru yang mengajar ABK tidak lagi menyesuaikan diri dengan pengaturan yang ada, tetapi harus menyesuaikan dengan kebutuhan anak. Sehingga pendidikan inklusif yang dibutuhkan oleh peserta didik berkebutuhan khusus memberikan kesempatan keluarga, guru, dan masyarakat terlibat dalam pembelajaran anak (Page et al, 2021). Disamping itu, melihat kebutuhan layanan pendidikan khusus bagi sekolah dasar di Kecamatan Kepulauan Seribu Utara dan selatan haruslah melibatkan semua anak tanpa memandang perbedaan lingkungan.…”
Section: Volunclassified
“…Guru yang mengajar ABK tidak lagi menyesuaikan diri dengan pengaturan yang ada, tetapi harus menyesuaikan dengan kebutuhan anak. Sehingga pendidikan inklusif yang dibutuhkan oleh peserta didik berkebutuhan khusus memberikan kesempatan keluarga, guru, dan masyarakat terlibat dalam pembelajaran anak (Page et al, 2021). Disamping itu, melihat kebutuhan layanan pendidikan khusus bagi sekolah dasar di Kecamatan Kepulauan Seribu Utara dan selatan haruslah melibatkan semua anak tanpa memandang perbedaan lingkungan.…”
Section: Volunclassified
“…Studies from different countries on educational challenges, specifically on children experiencing learning difficulties [7,[12][13][14][15][16], have shown that the problems encountered are quite universal; however, some specific characteristics may emerge due to national contexts.…”
Section: Introductionmentioning
confidence: 99%
“…People with other intellectual disabilities may suffer from changes in their routines that compel them to confront completely unknown situations. Disruptions in habitual activities can lead to emotional and behavioral upheaval ( Eshraghi et al, 2020 ; Page et al, 2021 ). Second, school closures can exacerbate the stress felt by family members of students with intellectual disabilities because, in such situations, they must exclusively shoulder the responsibility for providing support to their wards ( Fontanesi et al, 2020 ; Navas et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the pandemic accelerated innovations in online learning ( Ng, 2020 ), learning at home is relatively difficult for these students. Page et al (2021) summarized key challenges for students with special educational needs vis-à-vis their adoption of online learning methodologies or distance education. These challenges are listed as follows: access and use of technological tools; students’ engagement and changes to routine; risk of further isolation; falling behind in their learning; and significant risk of academic and emotional disconnect.…”
Section: Introductionmentioning
confidence: 99%